The Effect of Boiling Duration on The Antioxidant Activity of Green Mustard (Brassica rapa L.) - Prasetya, Landung Wahyu; Wahyuni, Sri; Mahmudah, Nur; Fithriya, Sa’idatul (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Background: A study stated that one of the contents of green mustard is phenolic which acts as an antioxidant. Antioxidant activity is influenced by the processing method, especially boiling. The duration of boiling can cause damage to antioxidant compounds. Outcome: This study was to determine the effect of the duration of boiling green mustard on the antioxidant activity contained in it. Method: This study used a laboratory experimental method with a post-test only controlled group. Results: The results of testing on fresh green mustard, green mustard boiled for 2-4 minutes showed an increase in IC50 value from 4,414.03E + 48 ppm to 5.3805E + 138 ppm. Green mustard boiled for 6 minutes experienced a decrease in IC50 value from 5.3805E + 138 ppm to 2,505.23E + 45 ppm. The IC50 value of green mustard boiled for 8 minutes increased again to 5,051.02E + 48 ppm. Boiled mustard greens for 10 minutes had a significantly decreased IC50 value to 0.0469 ppm. Conclusion: The effect of the duration of boiling green mustard greens (Brassica rapa L.) on the antioxidant effects contained there in. The duration of boiling green mustard greens (Brassica rapa L.) which has good antioxidant activity in green mustard greens boiled for 10 minutes.Keyword: Green Mustard, Phenolic, Antioxidant, Post Test Only Controlled Group